In vitro study on the antimicrobial effect of hydroalcoholic extracts from Mentha arvensis L. (Lamiaceae) against oral pathogens - doi: 10.4025/actascibiolsci.v34i4.8959 (Acta Scientiarum. Biological Sciences, 2012)
In vitro tests could be a valuable tool for the evaluation of medicinal plants’ antimicrobial activity. Mentha arvensis of the Lamiaceae family is one of the most frequently traditional plants used in Brazil. Hydroalcoholic extracts of M. arvensis were analyzed for antimicrobial activity on Streptococcus mutans, Streptococcus sobrinus and Candida albicans. Three different assays (agar diffusion, broth macro- and micro-dilution methods) were used to evaluate antimicrobial activity. Although hydroalcoholic extracts of M. arvensis did not show any antibacterial effect, its antifungal activity against C. albicans was revealed. According to the micro-dilution broth assay, MIC of the hydroalcoholic extract from leaves of M. arvensis on Candida albicans strains ranged between 625 and 2500 mg mL-1. Results suggest that M. arvensis hydroalcoholic extract may be considered a potentially antifungal agent against C. albicans, and a possible item for human antibiotic therapy.  However, further biological tests on the plant’s efficacy and side-effects are necessary before its use on humans.